"The drought, the State and the people; an experience in Gujarat-2000" - "South Asia Network on Dams, Rivers and People" (Pune, 2000)
Gujarat's drought -2000 was different in many ways . Most significantly, pro-large dams lobby made all possible efforts to get mileage for their pet Sardar Sarovar Project from this cruel tragedy, in many ways triggered by that project itself. However, everyone from the President of India to media to people and even Gujarat's Chief Minister (though rather reluctantly) had one central message to convey, either through their words or deeds. The message was that the solution to the deepending hydrological crisis was in people centered and people initiated rain water-harvesting systems.
Keywords: Droughts-Gujarat